Isolation of 10 differentially expressed cDNAs in p53-induced apoptosis: activation of the vertebrate homologue of the drosophila seven in absentia gene. - Amson, R B (1996)
We report the isolation of 10 differentially expressed cDNAs in the process of apoptosis induced by the p53 tamor suppressor. As a global analytical method, we performed a differential display of mRNA between mouse M1 myeloid leukemia cells and derived clone LTR6 cells, which contain a stably transfected temperature-sensitive mutant of p53. At 32 degrees C wild-type p53 function is activated in LTR6 cells, resulting in programmed cell death. Eight genes are activated (TSAP; tumor suppressor activated pathway), and two are inhibited (TSIP, tumor suppressor inhibited pathway) in their expression. None of the 10 sequences has hitherto been recognized as part of the p53 signaling pathway. Three TSAPs are homologous to known genes. TSAP1 corresponds to phospholipase C beta 4. TSAP2 has a conserved domain homologous to a multiple endocrine neoplasia I (ZFM1) candidate gene. TSAP3 is the mouse homologue of the Drosophila seven in absentia gene. These data provide novel molecules involved in the pathway of wild-type p53 activation. They establish a functional link between a homologue of a conserved developmental Drosophila gene and signal transduction in tumor suppression leading to programmed cell death.